Public Opinion on the Role of Committees in Environmental Impact Assessment Studies - Pletikosić, Merica; Majda Tafra Vlahović (European Journal of Social Science Education and Research, 2016)
The objectivity of expert committees working on environmental impact assessment studies is under intense public scrutiny. Citizens are often concerned about the potential impact of planned interventions on people’s health and the environment, which is why constant and stable communication should be maintained between all interested parties. Expert committees are in charge of addressing concerns coming from the public, private, and civil sectors by keeping communication channels open, efficient, and accessible. The importance of public participation in the procedures of environmental impact assessment is constantly growing, and expert committees involved in decision-making processes related to the assessment of environmental impact studies are exposed to increasing pressure from the public, economic, and civil sectors. This paper presents the results of empirical research on the knowledge and opinions of the concerned public in the Republic of Croatia on the role of expert committees in environmental impact assessment studies. The qualitative study was carried out using a purposive sample and the methods of in-depth interview and participant observation. The grounded theory method was used in the analysis of the empirical material and the quantification of the qualitatively processed coded material was carried out with the Statistica software suite (ver 11. 00). Participants were polarised in their opinions. Some of the participants believe that expert committees cannot be neutral as they are appointed by the Ministry. On the other hand, a number have stated that they believe the committees to be professional and neutral, that we should maintain trust in public institutions and that committee members should not be in any way associated with or related to the investors behind a particular project. The majority of participants from the public sector agrees with this positive opinion of the committees as neutral and professional, as does the majority of the economic sector. Participants from the civil sector, on the other hand, have mostly claimed that the committees are not neutral, but are either for or against a project, and that public interest has not been clearly defined in this context.
Keywords: local government, environmental impact assessment, public knowledge